BILATERAL SOCIAL DIALOGUE IN THE EDUCATION SECTOR IN LATVIA DURING THE COVID-19 PANDEMIC - Vanaga, Inga; Grinfelde, Anda; Paula, Liga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In 2020, the world was unprepared for the spread of the coronavirus pandemic. , . In Latvia, respective decisions and restrictions were made at the national, municipal and educational institution’s level, as it was important to respond promptly, flexibly and in accordance with the individual’s health security to ensure safe educational process. During the Covid-19 pandemic, distance learning was provided at most educational institutions, which was not a common practice until now. It facilitated the digitalisation of education, led to rapid adaptation to change and learning to work in times of crisis and limited resources. In the paper, theoretical findings of human capital and the agent network theory are used to reflect the provision of professional support for teachers and to analyse the implementation of cooperation or bilateral social dialogue during the state of emergency in Latvia. In 2020, the Latvian Trade Union of Education and Science Employees conducted two surveys of teachers of pre-school, general, vocational and higher education institutions on the quality of professional life during the state of emergency. The most important factors influencing professional work are as follows: technical equipment of the study process and digital skills; organization of the work of the study process; ensuring cooperation with students and colleagues; observance of teachers’ rights; protection against the risk of developing Covid - 19. Teachers working during the Covid-19 pandemic, essential provision of information technology, accessible and high-quality Internet, development of digital skills, reimbursement of teleworking, samples of adapted teaching aids, methodological and psychological support, guarantees of employment stability, observance of labour law, professional crisis communication with the parties involved in the educational process (employer, colleagues, students, parents).